Detección de ADN porcino en productos cárnicos comerciales por qPCR - Guidi, Silvina Mabel; Ambrosi, Vanina; Dolosa, Sasha; Nanni, Mariana Sandra; Diaz, Gabriela Esther (Asociación Argentina de Tecnólogos Alimentarios (AATA), 2023)
Poster